Magnetically Manipulable Ionic Liquid Crystals Incorporating Neutral Radical Moiety. Issue 3 (12th October 2021) - Uchida, Yoshiaki; Sakaguchi, Tatsunori; Oki, Shigeaki; Shimono, Satoshi; Park, Jayeong; Sugiyama, Masahito; Sato, Shuichi; Zaytseva, Elena; Mazhukin, Dmitrii G.; Tamura, Rui
Abstract: With a view to fabricating a new remote input‐output system by applying functional ionic liquid crystalline (ILC) materials, we have developed novel ILC compounds containing a nitroxide radical unit in the organic cations, which show an enantiotropic smectic A (SmA) phase. We have implemented the magnetic manipulation of a droplet of one of the ILC compounds on the basis of the intermolecular magnetic interactions between radical moieties. This ILC monoradical compound shows a 55 % larger increase in paramagnetic susceptibility at the solid‐to‐LC melting point in the first heating process than the non‐ionic LC monoradical compounds. It is most likely owing to the nanosegregation of strongly bonded ionic and non‐ionic moieties. The increased molar magnetic susceptibility is preserved not only in the SmA phase but also in the isotropic liquid and solid phases during the first cooling process. Abstract : The synthesis of a new ionic liquid crystal with a nitroxide radical moiety and the magnetic manipulation of a droplet of the compound are described in this work. The successful magnetic manipulability is most likely owing to the nanosegregation of strongly bonded ionic and non‐ionic moieties. Such a remote controllability would expand the applicability of the functional periodic structure in the ionic liquid crystals.